The effectiveness of teach using pictures and who are not teach without using pictures In Teaching Writing ( Study Case at SMPN 2 Kota Bima Grade VIII in Academic year 2022/2023 ) - Rizkiani, Firliah; Rifai, Rifai; Firmansyah, Firmansyah; Budiman, Arif; Hendra, Hendra (Jurnal Ilmiah Mandala Education (JIME), 2022)
The objectives of this research are to explain the effectiveness of using pictures in teaching writing at SMP Negeri 2 Kota Bima and to find out whether there is Is there a significant difference in the writing ability between the second grade students of SMP Negeri 2 Kota Bima who are taught by using pictures and those who are not taught by using pictures. This research is an experimental research study that was held in SMP Negeri 2 Kota Bima. The research subject was the second grade students. Population of students was 213. The experimental research involved one experimental group compared with the control group. Class B belongs to the control group taught without pictures and class A belongs to the experimental group taught trough pictures. Both classes were given a pre-test at the beginning. The post-test were given at the end of the meeting. For collecting the data the researcher applied writing test and the data were analyzed by applying t-test computation, descriptive and inferential analysis.